The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1414-431x20165252
|View full text |Cite
|
Sign up to set email alerts
|

Serum total bilirubin levels are negatively correlated with metabolic syndrome in aged Chinese women: a community-based study

Abstract: We evaluated serum total bilirubin levels as a predictor for metabolic syndrome (MetS) and investigated the relationship between serum total bilirubin levels and MetS prevalence. This cross-sectional study included 1728 participants over 65 years of age from Eastern China. Anthropometric data, lifestyle information, and previous medical history were collected. We then measured serum levels of fasting blood-glucose, total cholesterol, triglycerides, and total bilirubin, as well as alanine aminotransferase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…We also found that Mttp levels were low in Ppara HepKO mice, suggesting that Mttp is regulated via PPARα (Stec et al, 2019). Previous studies have shown a negative correlation between serum total bilirubin levels and blood triglyceride levels (Zhong et al, 2017;Petelin et al, 2020). Interestingly, in obese patients with low serum total bilirubin and higher triglycerides than lean control with bariatric surgery increased plasma bilirubin by two-fold and reduced triglycerides by 50% (Bawahab et al, 2017), illustrating the potential role of bilirubin in triglyceride metabolism.…”
Section: Discussionsupporting
confidence: 67%
“…We also found that Mttp levels were low in Ppara HepKO mice, suggesting that Mttp is regulated via PPARα (Stec et al, 2019). Previous studies have shown a negative correlation between serum total bilirubin levels and blood triglyceride levels (Zhong et al, 2017;Petelin et al, 2020). Interestingly, in obese patients with low serum total bilirubin and higher triglycerides than lean control with bariatric surgery increased plasma bilirubin by two-fold and reduced triglycerides by 50% (Bawahab et al, 2017), illustrating the potential role of bilirubin in triglyceride metabolism.…”
Section: Discussionsupporting
confidence: 67%
“…Several cross-sectional and longitudinal studies have reported an inverse association between serum TBil and MetS [ 10 , 11 , 14 , 21 ]. For example, a recent cross-sectional study involving 12342 adults in Korean suggested that elevated serum TBil was associated with a decreased risk of MetS [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported many related risk factors associated with the incidence of MetS [7][8][9], such as uric acid (UA), γ-glutamyl transpeptidase (GGT), and alanine aminotransferase (ALT). However, there are few studies grouping these factors to develop a model and predict the risk of MetS.…”
Section: Introductionmentioning
confidence: 99%